A dual inhibitor of TrxR1 and XIAP induces pyroptosis in melanoma - Wang, Yuan; Li, Xiangmei; Dong, Xinyue; Yuan, Haokun; Fang, Ruiqin; Zhang, Ran; Wang, Wei-jia (Frontiers in Cell and Developmental Biology, 2025)
Malignant melanoma ranks among the most aggressive forms of cancer, with high rates of metastasis and recurrence, as well as a poor prognosis. Consequently, an urgent need is to develop novel precision therapeutic strategies and corresponding drugs. Previous studies have shown that both X-linked inhibitor of apoptosis (XIAP) and thioredoxin reductase 1 (TrxR1) participate in the resistance of melanoma to chemotherapy-induced cell death. In this study, we designed and synthesized a series of derivatives of natural compounds derived from Toona sinensis to simultaneously inhibit TrxR1 activity and destabilize the XIAP protein. The new dual-target inhibitor TRI-03 has significant antiproliferative effects on melanoma cells. Mechanistically, TRI-03 not only increases intracellular reactive oxygen species (ROS) levels by inhibiting TrxR1 activity but also decreases XIAP expression, leading to the activation of the caspase-9/caspase-3/GSDME axis and irreversible GSDME-mediated pyroptosis in melanoma cells. Our in vivo animal study confirmed that TRI-03 effectively inhibits melanoma proliferation and metastasis without severe side effects. Therefore, our study identified TRI-03 as a potential antitumor candidate for future development to address melanoma.